School Administrators in Basic Education in Nigeria - Ogunode, Niyi Jacob; Mbata , Felicia Oganeze; AYOKO, Victor Olugbenga (Researchparks Publishing, 2023)
This paper discussed the challenges Basic school administrators are facing in Nigeria. Secondary data were employed in the presentation. The data were collected from both print and online publications. The paper concluded that inadequate funds, Shortage of professional teachers, inadequate infrastructure facilities, insecurity problems, shortage of instructional materials, poor motivation and a high population of students are some of the challenges Basic school administrators are facing in Nigeria. To solve the challenges, the paper hereby recommended increment in the funding of Basic schools, employment of more teachers, provision of more infrastructure facilities, and instructional materials, motivation of school administrators and provision of adequate security in Basic schools.